Fetal and maternal lesions of cyanide dosing to pregnant goats - Soto-Blanco, Benito; Pereira, Flávia Thomaz Verechia [UNESP]; de Carvalho, Ana Flavia; Miglino, Maria Angelica; Gorniak, Silvana Lima (Elsevier B.V., 2009)
The present work evaluated the pathological effects in both dams and their fetuses of cyanide ingestion during pregnancy using goat as animal model. From the Day 24 of pregnancy, three pregnant goats were dosed by gavage with 3.0 mg KCN/kg bw/day, and two others received only tap water. All dams were euthanized and necropsied at Day 120 of pregnancy. The fetuses were examined carefully for gross abnormalities. Determinations of cyanide and thiocyanate were performed in maternal and fetal blood and in amniotic fluid. Samples of several organs were collected for histopathologic evaluation. No clinical changes were seen in any animal throughout the pregnancy. No malformations or dead fetuses were observed: however, placenta from one treated goat presented increased cotyledon surface area occupied by vascular lumina. Histological lesions in KCN-treated dams consisted of vacuolation of hepatocytes and thyroid follicular cells, increased number of vacuoles on thyroid follicular colloid. and spongiosis of cerebral, internal capsule, and cerebellar peduncles tracts. Fetuses from these mothers showed vacuolation of hepatocytes and thyroid follicular cells, and spheroids in the cerebellar white matter. Levels of cyanide and thiocyanate were higher in maternal than fetal blood, which suggests that these substances were largely but not freely transferred from mothers to fetuses. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cyanide; Placenta; Teratology; Reproductive toxicology; Ruminants